In Vitro Evolution and Preliminary Characterization of a Cadmium-Resistant Population of Chlamydomonas reinhardtii - Nagel, Klaus (1989)
A cadmium-tolerant population of Chlamydomonas reinhardtii was derived from a Cd-sensitive cell wall-deficient strain by long-term selection in liquid culture. A comparison of Cd-sensitive and Cd-tolerant cells revealed that Cd tolerance was due to genetically determined alterations of metabolism rather than to increased efficiency of a detoxification system.